2022
DOI: 10.3390/antibiotics11091191
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review with Trial Sequential Analysis of Prophylactic Antibiotics for Acute Pancreatitis

Abstract: Background/Objectives: Prophylactic antibiotics (PAB) are being still widely used for treatment of acute pancreatitis (AP) despite trials showing no firm evidence of efficacy. We aimed to evaluate effects of PAB for AP in a meta-analysis and the need for further research by trial sequential analysis (TSA). Methods: Medline, Scopus and Web of Science were searched for randomized clinical trials. Primary outcomes were all infections and mortality. Secondary outcomes comprised infected pancreatic necrosis (IPN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
8
0
3
Order By: Relevance
“…However, conflicting results have been reported in the literature due to different methodologies ( 22 ). Most published studies supported that there may be a negative association between antibiotic prophylaxis and the risk of necrotic tissue infection ( 19 - 21 ). In 2010, Villatoro et al reported that prophylactic imipenem, unlike other antibiotics, reduces the risk of pancreatic infection ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conflicting results have been reported in the literature due to different methodologies ( 22 ). Most published studies supported that there may be a negative association between antibiotic prophylaxis and the risk of necrotic tissue infection ( 19 - 21 ). In 2010, Villatoro et al reported that prophylactic imipenem, unlike other antibiotics, reduces the risk of pancreatic infection ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of prophylaxis on non-pancreatic infections is controversial. Although some meta-analyses determined that prophylaxis reduced the infection, especially urinary tract infections and sepsis ( 19 , 20 ), some meta-analyses found antibiotic prophylaxis did not affect infection ( 21 ). Our meta-analysis showed that carbapenems were related to a lower risk of non-pancreatic infection risk in all subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Діагностика, зокрема оцінка тяжкості стану дитини з гострим деструктивним панкреатитом, і навіть лікувальна тактика, залишаються предметом дискусії. Загальні діагностичні маркери, як-то -визначення активності панкреатичних ферментів у крові, сечі, перитонеальному та торакальному секреті, динаміка гомеостатичних показників, а також комплексне інструментальне обстеження (УЗД органів живота, комп'ютерна томографія та магнітно-резонансна томографія, відеохірургічна діагностика), є стандартними як щодо дорослого, так і щодо педіатричного стаціонару [2,3,4,8,12,19,22,23]. У той же час ендоскопічна візуалізація фатерова сосочка та ретроградна панкреатохолангіографія (ЕРПХГ), а за показаннями -ендоскопічна дуоденопапілотомія, не знайшли належного застосування в умовах дитячого хірургічного стаціонару [9,13].…”
Section: вступunclassified
“…Так само, на відміну від дорослих пацієнтів, має свої особливості лікувальна тактика у дітей із гострим деструктивним панкреатитом. Статистичні дослідження свідчать, що загальна летальність у дітей із гострим панкреатитом становить 2,1%, а у дітей із гострим деструктивним панкреатитом летальність сягає 50% [17,19,23].…”
Section: вступunclassified
See 1 more Smart Citation